PERANCANGAN ALAT PENCEKAM UNTUK PEMESINAN POLYURETHANE FOAM PADA PROSES FACE MILL CUTTING MESIN CNC ROUTER 3 AXIS DENGAN METODE VDI 2221 - Utomo, Archi Kun Cahyo; Ubaidillah, Ubaidillah; Raharjo, Wijang Wisnu; Fitrian Imaduddin; Dikky Kusuma Wijaya (Jurnal Rekayasa Mesin, 2024)
Due to the highly brittle structure of polyurethane (PU) foam, a specialized clamping mechanism is required to consider the material's strength and hardness to avoid damaging the workpiece and to withstand the cutting forces during milling and machining. Using a polymer as an alternative for creating clamping tools with characteristics similar to PU foam offers a promising solution. The slightly harder polymer material is expected to address the need for a gripping tool that will not harm the PU foam upon application. The VDI 2221 method, a structured approach to the design and coordination of evolving design techniques, is employed in this study. The advantage of this methodology lies in its ability to adapt continuously through research. A comparative analysis of two design models produced via 3D printing reveals that Design 5 exhibits superior strength under increased stress. Moreover, Design 5 is more effective in gripping the workpiece, as a single gripper can withstand cutting forces from two directions simultaneously, reducing material deformation. This advancement is expected to minimize the risk of material damage during the machining process. This research's novelty lies in applying an optimized polymer clamping device for PU foam, ensuring improved performance and reduced damage during machining.